International management and international relations : a critical perspective from Latin America - Faria, Alex , 1963-; Guedes, Ana , 1964- (Management, organizations and society (London, England), 2010)
Shows that interdisciplinary developments between the previously distinct fields of International Management (IM) and International Relations are important for the construction of a Latin America perspective in the field of International Management, contributing to the development of the IM field in other parts of the world